P75NTR, but Not proNGF, Is Upregulated Following Status Epilepticus in Mice. (24th September 2014) - VonDran, Melissa W.; LaFrancois, John; Padow, Victoria A.; Friedman, Wilma J.; Scharfman, Helen E.; Milner, Teresa A.; Hempstead, Barbara L.
ProNGF and p75 NTR are upregulated and induce cell death following status epilepticus (SE) in rats. However, less is known about the proneurotrophin response to SE in mice, a more genetically tractable species where mechanisms can be more readily dissected. We evaluated the temporal- and cell-specific induction of the proneurotrophins and their receptors, including p75 NTR, sortilin, and sorCS2, following mild SE induced with kainic acid (KA) or severe SE induced by pilocarpine. We found that mature NGF, p75 NTR, and proBDNF were upregulated following SE, while proNGF was not altered, indicating potential mechanistic differences between rats and mice. ProBDNF was localized to mossy fibers and microglia following SE. p75 NTR was transiently induced primarily in axons and axon terminals following SE, as well as in neuron and astrocyte cell bodies. ProBDNF and p75 NTR increased independently of cell death and their localization was different depending on the severity of SE. We also examined the expression of proneurotrophin co-receptors, sortilin and sorCS2. Following severe SE, sorCS2, but not sortilin, was elevated in neurons and astrocytes. These data indicate that important differences exist between rat and mouse in the proneurotrophin response following SE. Moreover, the proBDNF and p75 NTR increase after seizures in the absence of significant cell death suggests that proneurotrophin signaling may play other roles following SE.